The History of Water in the Land Once Called Palestine : Scarcity, Conflict and Loss in Middle East Water Resources /: Scarcity, Conflict and Loss in Middle East Water Resources. (2021) - Ward, Christopher; Ruckstuhl, Sandra; Learmont, Isabelle
No abstract available